Studies of gallium nitride high electron mobility transistors - Goh, Basil Yan Kun (2016)
Gallium Nitride (GaN) is a Group III/V wide bandgap nitride-based material that possesses many unique properties, which pushes semiconductor device performances to newer limits. This has been attracting attention in both the engineering field and the commercial semiconductor industry. With the ability to achieve very high cut-off frequency, low noise figure and high power output density performance in fabricated devices, GaN is set to be one of the most advanced semiconductor materials for a wide spectrum of existing and new applications.